2012
DOI: 10.3382/ps.2012-02273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and characteristics of the formation of different adipose tissues in ducks during early growth

Abstract: The objective of the current research was to investigate the pattern of subcutaneous adipose tissue growth during Peking duck (Anas platyrhynchos) early development and to determine the reasons for regional differences. The morphological characteristics in 5 regions of subcutaneous tissue, including the neck area (NSF), chest area (CSF), lower abdomen area (ASF), back area (BSF), and leg area (LSF), were analyzed by comparing the morphology of the sections, adipocyte volume and number, and lipid content from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…However, like 39ºC, egg incubation at 36°C also reduced the size of neck adipocytes, but its effect was less pronounced because adipocytes were only approximately 30% smaller compared to 37.5°C. Since adipocyte hypertrophy is directly related to fat deposition ( Tchernof et al, 2006 ; Kou et al, 2012 ; Choe et al, 2016 ), this supports the idea that high incubation temperature induced a decrease in fat deposition in neck and abdominal adipocytes, while a low incubation temperature induced increased deposition in thigh and abdominal adipocytes and a decreased deposition in neck adipocytes. From a developmental view, our results are of great interest and importance because they reveal a close link between egg incubation temperature during fetal development and postnatal adiposity in broilers.…”
Section: Discussionsupporting
confidence: 55%
“…However, like 39ºC, egg incubation at 36°C also reduced the size of neck adipocytes, but its effect was less pronounced because adipocytes were only approximately 30% smaller compared to 37.5°C. Since adipocyte hypertrophy is directly related to fat deposition ( Tchernof et al, 2006 ; Kou et al, 2012 ; Choe et al, 2016 ), this supports the idea that high incubation temperature induced a decrease in fat deposition in neck and abdominal adipocytes, while a low incubation temperature induced increased deposition in thigh and abdominal adipocytes and a decreased deposition in neck adipocytes. From a developmental view, our results are of great interest and importance because they reveal a close link between egg incubation temperature during fetal development and postnatal adiposity in broilers.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast to broiler chickens, we found that the TG content in SAT and AAT showed a“rise, decline and rise” trend. The discrepancy may result from our use of samples from multiple regions of adipose tissue rather than from a single specific location, as described by Kou et al (2012) . As the TG content reflects the fat storage capacity, our findings suggest that AAT may display greater fat storage capacity than the SAT from P28 to P120.…”
Section: Discussionmentioning
confidence: 99%
“…Peking duck (Anas platyrhynchos) is a world famous waterfowl breed that is able to accumulate large quantities of lipid in the subcutaneous adipose tissue (Attia et al 2012;Ding et al 2012). It has been well established that the development of duck adipose tissue is due to a combination of adipocyte hyperplasia and hypertrophy from hatching until 4 weeks of age, after which adipose expansion is accomplished exclusively by adipocyte hypertrophy (Kou et al 2012). However, the molecular mechanism involving the growth and differentiation of duck preadipocytes remains unknown.…”
Section: Introductionmentioning
confidence: 99%